2015
DOI: 10.1039/c5ay01288k
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid and simple LC-MS/MS method for identification and quality control of natural Calculus bovis and Calculus bovis sativus

Abstract: Calculus bovis sativus (C. bovis sativus, CBS), with the same pharmacodynamics activities as those of natural C. bovis (CB), has been approved as an ideal substitute in China. However, in the latest edition of the Chinese Pharmacopoeia, only cholic acid and bilirubin are used as the markers for quality control. To overcome current limitations and to further improve its quality control method, a rapid and reliable method was herein developed for simultaneous qualitative and quantitative analyses of taurine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Calculus Bovis Sativus (Lot: 2016–05-16) was provided by Wuhan Jianmin Dapeng Pharmaceuticals Co., Ltd., (Wuhan, China), and dissolved in normal sterile saline. The effective components (taurine and bile acids) in CBS were quantified by a HPLC-MS/MS approach described in our previous study [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculus Bovis Sativus (Lot: 2016–05-16) was provided by Wuhan Jianmin Dapeng Pharmaceuticals Co., Ltd., (Wuhan, China), and dissolved in normal sterile saline. The effective components (taurine and bile acids) in CBS were quantified by a HPLC-MS/MS approach described in our previous study [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bile acids, bilirubin, and taurine are considered the main effective components in CBS [ 38 , 41 ]. In our previous work, we simultaneously quantified taurine and 12 bile acids using high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) to control the quality of CBS [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBS and natural CB are similar in characteristics, ingredients, contents, and therapeutic effects. 10 Although the therapeutic effects of CB and CBS in the liver are well documented, the underlying mechanism of action has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Given that Calculus Bovis is insufficient of nature sources, Calculus Bovis Sativus (Tiwai Peiyu Niuhuang, CBS) was invented as the substitute in the medicinal preparations. Many studies have shown that CBS shares basically the same property, structure, composition, content, and clinical efficacy with those of Calculus Bovis [68]. Moreover, because of its complex components including bilirubin, cholic acid, bile acids and cholesterol, and so forth, we have established HPLC fingerprints for the effective quality control of CBS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that CBS shares basically the same property, structure, composition, content, and clinical efficacy with those of Calculus Bovis [68]. Moreover, because of its complex components including bilirubin, cholic acid, bile acids and cholesterol, and so forth, we have established HPLC fingerprints for the effective quality control of CBS [8]. Our previous study indicated that CBS treatment had a beneficial effect on 17 α -ethynylestradiol- (EE-) induced intrahepatic cholestasis rats and significantly increased the mRNA and protein expressions of multidrug resistance-associated protein 2 (MRP2) and breast cancer resistance protein (BCRP), both important proteins on the apical membrane of hepatocytes involving in the transport of bile acids, bilirubin, drugs, and so on [9].…”
Section: Introductionmentioning
confidence: 99%